2018
DOI: 10.18203/2394-6040.ijcmph20182178
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of hypertension and their risk factors in fishermen of Chennai district

Abstract: Background: Hypertension is one of the major public health issues in worldwide. The objective of this study was to find out the prevalence of hypertension and its associated risk factors in fishermen of Chennai district, Tamil Nadu, India.Methods: The cross sectional study was conducted among 519 fishermen at the coastal areas of north Chennai district selected by multistage cluster sampling method.Results: In our present study, the significantly associated with the factors included age, level of education, ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Many cross-sectional studies among fishermen community showed the significant association between diabetic, hypertension and cigarette smoking, tobacco chewing, alcohol consumption. 7,[12][13][14] In the present study proportion of harmful life style practices were 5.4 times higher among those had inadequate sleep (<6 hour). This study findings were similar to the findings were shown in A systematic review of the literature on night work and alcohol consumption by Richter et al 15 A study on correlation between shift-workrelated sleep problems and heavy drinking in Japanese male factory workers showed that tobacco consumption was higher among those workers on shift basis.…”
Section: Resultsmentioning
confidence: 82%
“…Many cross-sectional studies among fishermen community showed the significant association between diabetic, hypertension and cigarette smoking, tobacco chewing, alcohol consumption. 7,[12][13][14] In the present study proportion of harmful life style practices were 5.4 times higher among those had inadequate sleep (<6 hour). This study findings were similar to the findings were shown in A systematic review of the literature on night work and alcohol consumption by Richter et al 15 A study on correlation between shift-workrelated sleep problems and heavy drinking in Japanese male factory workers showed that tobacco consumption was higher among those workers on shift basis.…”
Section: Resultsmentioning
confidence: 82%
“…Indonesia has a large coastal area and has the most islands in the world and 60% of Indonesia's population lives in coastal areas (BPS, 2016). The prevalence of hypertension in coastal areas is quite high, such as in China at 21.5% (Chen et al, 2014), India at 46.6% (Muthukrishnan, Pillai Uma, & V., 2018), Brazil at 44% (Begossi, 2013). A literature study that the prevalence of hypertension specifically in coastal areas ranged from 6.45% to 51.1% (Yodang & Nuridah, 2019).…”
Section: Introductionmentioning
confidence: 99%